A Comparison of Clinical Outcomes and Implant Preference of Patients with Bilateral TKA: One Knee with a Patient-Specific and One Knee with an Off-the-Shelf Implant. Issue 2 (4th February 2022) - Schroeder, Lennart; Dunaway, Andrew; Dunaway, Daniel
Abstract : Background: The purpose of this retrospective study was to compare clinical outcome results, perceived function, and overall preference among patients who had undergone staged bilateral total knee arthroplasty (TKA) with a cruciate-retaining, customized implant (customized TKA, or C-TKA) in 1 knee and an off-the-shelf (OTS) implant in the contralateral knee. Methods: Forty-seven patients (94 knees) from a single study center who underwent C-TKA in 1 knee and had previously undergone TKA with an OTS implant in the contralateral knee were included in this study. As the primary outcome measures, the Knee injury and Osteoarthritis Outcome Score, Joint Replacement (KOOS, JR) and the Forgotten Joint Score (FJS) were self-administered by the study subjects at a single follow-up time point. Additionally, a follow-up questionnaire to compare patients' perceived joint stability, knee mobility, perceived feeling of the replaced joint, pain levels, and overall preference between their knees was administered. Results: The average follow-up was 2.3 years (range, 0.7 to 3.8 years) for C-TKA and 6.7 years (range, 1.6 to 11.1 years) for the OTS TKA. Significantly higher KOOS, JR (82 versus 77; p = 0.03) and FJS (68 versus 58; p = 0.04) results were found with C-TKA. The evaluation of the follow-up questionnaire showed that more patients reported having "a little" or "a lot" less pain (49% versus 15%), better perceived mobility (45% versus 12%) and stability (36% versus 13%), and a more "normal" feeling of their knee (60% versus 10%) with the C-TKA implant compared with their OTS counterpart. When patients were asked to directly compare their knees, we found that 72.3% of the patients preferred the knee that received C-TKA over the contralateral OTS knee replacement, with 21.3% seeing no difference and 6.4% preferring the OTS knee replacement. Conclusions: We believe that this is the first study to examine patient-reported outcomes of customized and OTS TKA implant designs in the same patient. We conclude that patients in this study cohort who underwent staged bilateral TKA with a C-TKA implant in 1 knee and an OTS prosthesis in the other knee reported better for their patient-specific knee replacement, with higher FJS and KOOS, JR values, and overall, preferred the C-TKA knee more often compared with the OTS knee replacement. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.